Pengaruh Brand Image Terhadap Keputusan Berkunjung Wisatawan Nusantara Ke Sari Ater Hotel & Resort, Subang - Susanto, Anthonny; Laksana, Prashad Akbar; Prianka , Winda Gafrilia (Politeknik Pariwisata NHI Bandung, 2019)
Brand image (Brand Image) is a representation of the overall perception of the brand and is formed from information and past experience of the brand. The image of a brand is related to attitudes in the form of beliefs and preferences towards a brand. A good brand is a key to success for a company in achieving sales targets. The high level of competition, makes consumers have an attitude towards a brand (brand). Tourist destinations that have a positive image will further convince consumers to make a visit. Sariater Hotel & Resort as one of the very popular tourist destinations in Subang Regency always strives to maintain and improve all important aspects that are important so that tourists will come to visit. The goal is carried out by giving the best service, Sariater Hotel & Resort always makes a good brand image for tourists. In this study, the independent variable (X) used is the brand image which consists of the strength of the brand association, the benefits of the brand association and the uniqueness of the brand association, while the independent variable (Y) used is the decision to visit. This type of research is descriptive verification. The population in this study were all characteristics that visited Sariari Hotel & Resort. The sampling technique used is Nonprobability sampling by incidental sampling so that the sample obtained is 100 tourists visiting Sariater Hotel & Resort. Data analysis and hypothesis testing techniques used are multiple regression methods. The results showed that brand image had a significant effect on visiting decisions. The factor that most influences the visit decision is the strength of the brand association. This is supported because the information that enters the consumer's memory is very strong and the information survives as the brand image of the Sariater Hotel & Resort to increase the number of tourist visits.